Competitiveness Business - Palacios , Arturo (Revista Universidad de Guayaquil, 2008)
Today, companies are still in search of excellence and are constantly striving to align their employees within their organizations to the strategic objectives of the company, focusing on its mission, vision, values and objectives, without achieving the expected results, Maybe it is because we are not reaching our employees, or because we do not have the right leaders to promote the desired change, or maybe it is because the companies must overcome a series of obstacles associated with their internal processes, such as; suitable recruitment of personnel, or lack of a business budget that links real expectations of growth or maintenance to achieve the results expected by the shareholders.